Safety and bioactivity studies of Jasad Bhasma and its in-process intermediate in Swiss mice. (2nd February 2017) - Chavare, Aparna; Chowdari, Praneeth; Ghosh, Sandipto; Pawar, Priyanka; Patkar, Meena; Dakave, Suresh; Gota, Vikram; Chaudhari, Pradip; Chiplunkar, S.V.; Kane, Shantaram; Suresh, A.K.; Bellare, Jayesh
Abstract: Ethnopharmacological relevance: Bhasma, Ayurvedic medicinal preparations, are prepared using herbs and minerals on following long iterative procedures. However, industrially mercury and sulphur are more commonly used to prepare bhasma from its raw material. The end point of this iterative procedure is mainly judged by the traditional tests specifying physical appearance of the powders. They fail to give better idea about chemical nature of the material. Moreover, the differences in biological activity of final product verses intermediate are not addressed. Aim of the study: To compare the physicochemical as well as biological properties of the Jasad bhasma and its in-process intermediate using modern science methods. Materials and methods: The Jasad bhasma and its in-process intermediate are characterized for their physicochemical properties using electron microscopy, x-ray diffraction and CHNS(O) analysis. The biological effects of both the preparations are then studied. The bioaccumulation of zinc, effect on liver antioxidant status, liver and kidney function (by conventional tests as well as SPECT: Single Photon Emission Computed Tomography), effect on blood cells and effect on immune system are studied in mice model, Swiss albino . Since bhasma is given with an accompaniment ( anupan ), all the bioactivity studies were carried out by administering the preparation with and without Amala powder ( Phyllanthus emblica L., fruit, dry powder) as anupan . Results: The XRD results accompanied with Rietveld analysis indicate that the final bhasma is mainly oxide of zinc, whereas the intermediate is mainly sulphide of zinc. The animal studies show that the bhasma as well as its intermediate do not lead to any bioaccumulation of zinc in major organs, when administered with and without anupan . Both, bhasma and intermediate do not cause any deleterious effects on kidney and liver as indicated by blood biochemistry and SPECT studies. However, the intermediate perturbs antioxidant status more and affects the platelet turnover, in comparison with bhasma . On 28 day treatment, the bhasma treated animals show prominence of TH 1 mediated immune response whereas, intermediate treated animals show prominence of TH 2 mediated immune response. Conclusion: A set of simple modern microscopy and diffraction techniques can affirmatively identify in-process intermediate from the final preparation. These can be used to decide the end point of long and iterative preparation methods in accordance with modern science practices. The differences in physicochemical properties of particles from the two preparations reflect in their different biological effects. Moreover, the bhasma affects several components of biological systems which again in-turn interact with each other, which emphasizes the need of multifaceted studies in this field. Graphical Abstract: